Feasibility Analysis of Diesel Power Plant Operations (PLTD) in North Sumatra - Sihombing, Alex Wilesa; Erivianto, Dino; Dalimunthe, Muhammad Erpandi (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
Diesel Power Plants (PLTD) are a type of power plant that is widely used in various regions, especially in remote areas that are not yet reached by the PLN electricity network. This research aims to analyze the operation of the PLTD system, including operational efficiency, fuel consumption and its impact on the environment. This analysis uses a general approach based on relevant literature and case studies from several PLTDs in North Sumatra. The research results show that the efficiency of the PLTD system is very dependent on engine maintenance, fuel quality and operational loads. Although PLTD has advantages in terms of flexibility and ignition speed, the main challenges are the high operational costs and exhaust emissions from the PLTD engine.